ANALISIS PENGGUNAAN BAHAN PENGEMAS PADA PRODUK CERIPING SINGKONG BERDASARKAN HASIL UJI TARIK DAN UJI WVTR (WATER VAPOUR TRANSMISSION RATE) DI GNP SNACK MUNTILAN - , EFRILIA LENI E ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ceriping Singkong need high quality packaging materials to maintain productâs quality that unchanged in terms of taste, appearance and flavor. The quality of packaging can be determined by many tests such as Tensile test and WVTR (Water Vapour Transmission Rate) test. Tensile test is a method to determine the tensile strength of the plastic packaging through gravity and the length. WVTR test or water vapor permeability of packaging materials aims to determine the speed of moisture content through the layer thickness of certain packaging due to the difference in water vapor pressure between products with environmental temperature and specified relative humidity conditions. Packaging quality of Ceriping Singkong testing at the Laboratorium Analisis Mutu dan Standardisasi, Faculty of Agriculture Industrial Technology, University of Gadjah Mada. The results of both test can be used as reference for the proposed improvement of Ceriping Singkongâs product packaging is adapted by act No.18 of year 2012 on Food, that would be obtained the proposed improvements which protect the product, did not harm consumers and accordance with regulations government. Tensile strength on the Ceriping Singkong packaging is good, the packaging has the length and high compressive force. The water vapor permeability of packaging materials (WVTR) test on Ceriping Singkong products had low value, low value indicates that the container capable of holding water vapor and gases into the packaging. Proposed improvements of Ceriping Singkong product packaging consists of three design, which design 1 and 2 are simple plastic packaging from Polyethylene and design 3 is more modern packaging standing pouch shaped.